2019
DOI: 10.1007/jhep08(2019)028
|View full text |Cite
|
Sign up to set email alerts
|

Exact scattering amplitudes in conformal fishnet theory

Abstract: We compute the leading-color contribution to four-particle scattering amplitude in four-dimensional conformal fishnet theory that arises as a special limit of γ-deformed N = 4 SYM. We show that the single-trace partial amplitude is protected from quantum corrections whereas the double-trace partial amplitude is a nontrivial infrared finite function of the ratio of Mandelstam invariants. Applying the Lehmann-Symanzik-Zimmerman reduction procedure to the known expression of a four-point correlation function in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(78 citation statements)
references
References 45 publications
7
71
0
Order By: Relevance
“…Using Sommerfeld Watson transform as usually done in studying the Regge limit of QFT scattering amplitudes, we obtain the Regge poles of our correlator. This is presented in detail in section (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Sommerfeld Watson transform as usually done in studying the Regge limit of QFT scattering amplitudes, we obtain the Regge poles of our correlator. This is presented in detail in section (3).…”
Section: Resultsmentioning
confidence: 99%
“…A LLA (s, t) ∝ log s , (1.8) In [3], the author studies the Regge limit of the 0−magnon four point amplitude in the fishnet theory using standard LSZ reduction techniques in momentum space. An immediate obstruction to generalizing their method to the 1 and 2-magnon cases is the fact that the 1 and 2-magnon states describe a bound state which is off-shell.…”
mentioning
confidence: 99%
“…Since the theory is invariant under φ 1 → (φ 1 ) T , φ 2 → (φ 2 ) T , it suffices to consider the former class. In [19] it was shown that A 4 (1, 1) is tree-level exact; let us review the argument here. Figure 4 displays the tree-level contributions to A 4 (1, 1) from the single trace vertex and the double trace vertices proportional to α 2 2 , as well as the 1-loop diagram which receives contributions from both of these single and double trace vertices.…”
Section: Exact Half-track Amplitudesmentioning
confidence: 97%
“…Term-by-term, (5.21) is UV-divergent, but it is straightforward to see that the combination of all three terms is finite. This is the same mechanism that removes all divergences from the four-point single colour amplitudes (cf., [19]) at the conformal fixed point. On twistor space, the diagram corresponding to the first term in (5.21) evaluates to: at the conformal fixed point.…”
Section: Snowflake Amplitudesmentioning
confidence: 99%
See 1 more Smart Citation